The homeless population during the COVID-19 syndemic: Inequities, practices of social resilience, and social reintegration strategies - Bova, Roberta (Frontiers in Sociology, 2022)
This paper analyses the amplification of social insecurity and the social misrecognition of the homeless during the COVID-19 syndemic. The research was carried out in the city of Bergamo (IT), which has been severely affected by the COVID-19 syndemic since the early months of 2020; the research was developed in two phases. The first one analyses the practices of social resilience activated during the COVID-19 syndemic by the socio-educational staff and the coordination figures who work in the support services. The second phase analyses the different social dynamics that can improve the wellbeing and social reintegration of the homeless from a long-duration perspective. During the first months of 2020, the public authorities failed to pay attention to homeless people who slept on the streets and who lived in communities or found support in night shelters. The support services had to activate immediate emergency response strategies and subsequently had to produce and purchase protective devices for operators, guests and those who remained on the street. Faced with this process of social misrecognition, the support services for homeless people reacted by activating practices of social resilience. These practices have investigated the dimensions of daily interactions and the symbolic and value configurations connected to them. However, directly conversing with the homeless, it emerges that to achieve full social reintegration and to prevent new forms of social misrecognition, in the event of future social or health crises, the relationship with a non-stigmatized social community is fundamental. Consequently, the primary objectives that the support network for homeless people should set for future projects should involve the local community through project participation activities and raise awareness of the phenomenon of poverty.